NP Role and Patient Outcomes Are Supported by High-Level Evidence. Comment on Almutairi et al. Nurse Practitioner: Is It Time to Have a Role in Saudi Arabia? Nurs. Rep. 2020, 10, 41-47 - Julee B. Waldrop (MDPI AG, 2022)
This is a letter to the editor in response to the article titled "Nurse Practitioner: Is it Time to Have a Role in Saudi Arabia?" Clarifications on the nurse practitioner role definition and description, educational preparation, and quality and value of care are made and supported with authoritative, high-quality evidence.